Variable compression panel thickness for concrete members under bending and torsion: Experimental study. (15th March 2023) - Tulonen, Joonas; Laaksonen, Anssi
Highlights: Current models for the design of concrete members under combined action are lacking. Experiments on concrete beams under combined actions show signs of brittle failure. Strain measurements on compressive face show diagonal compression field behaviour. New space truss model with variable compression panel thickness is verified. Strength reduction factors for concrete under shear can be derived from the results. Abstract: An experimental study was conducted on the behaviour of eight reinforced and prestressed concrete beams subjected to combined action of bending and torsion. The beams were heavily reinforced in the longitudinal direction so that the height of the concrete compression zone under pure bending would be much larger than the concrete diagonal strut thickness under pure torsion and measurements were done so that behaviour of this compressive zone could be observed. The amount of the reinforcement was designed close to the over-reinforcement limits, as would happen if the cross-section dimensions of an actual structure would be minimized in the design. The ultimate resistances and beam deformations were compared against the results of a plasticity-based space truss model where the panel on the compressive side of the cross-section had variable thickness in order to account for the resultant force demands of both the bending and torsion. Most heavily reinforced beams failed in a brittle manner due to the ineffectiveness of diagonally cracked concrete to resist the high normal stresses arising from the bending. The proposed model gave better predictions than the classical model where the panel thickness was constant, and the results showed the significance of concrete strength reduction factor contribution in ultimate resistance of concrete members under combined bending and torsion.